Good Practices in City Energy Efficiency : Bogota, Colombia - Bus Rapid Transit for Urban Transport - World Bank (Washington, DC, 2014)
Bogota, the capital city of Colombia, is located near the geographic center of Colombia, 2,640 meters (8,661 ft) sea level. It is the largest and most populous city in the nation, with an estimated 8.2 million inhabitants in the metropolitan area in 2007 and a population density of 3,912 inhabitants per square kilometer. Its economy generates 25 percent of Colombia's total gross domestic product (GDP). The city's roads were highly congested with the significant growth in private car ownership and use. While private cars occupied 64 percent of the road space, they only represented 19 percent of the population, and the daily average commute time was 1 hour and 10 minutes each way. Other issues included high incidences of accidents and extremely high air pollution rates during peak travel hours. In 1999, after the new National Government rejected potential plans for a subway system, the Mayor of Bogota presented his plan for a Bus Rapid Transit (BRT) system, built upon the successful experience of Curitiba in Brazil. The transition to an effective BRT system would help realize the Mayor's four main goals by: (i) improving public transport system with respect to efficiency, safety, speed, convenience and comfort ensuring high rider-ship; (ii) restricting private automobile use; (iii) expanding and improving bicycle paths; and (iv) enhancing public space. The system improves upon Brazil's Curitiba system by operating without subsidies from public authorities. Fares were established at US$0.40 in 2000 and have been raised to US$0.61 in order to ensure that all costs of operations provided by private operators are covered. This was achieved through the successful implementation of a concession-based contract that aimed at regulating service operations and eliminating rents to avoid fare-hikes. The private operator can earn profits when demand for rider-ship increases and incurs cost in the case that the demand for rider-ship declines. The BRT provided the incentives for private operators to compete for specific route in terms of per-kilometer basis as opposed to a per-passenger basis.